2022
DOI: 10.55493/5002.v12i3.4441
|View full text |Cite
|
Sign up to set email alerts
|

Social Responsibility Accounting, Disclosure and Real Practice: Evidence from Jordan

Abstract: This study aims to present a true image of social responsibility accounting (SRA) in Jordanian companies listed on the Amman Stock Exchange (ASE). A survey questionnaire was employed to check the level of SRA practice, and a checklist was used to discover the level of SRA disclosure which was collected from the annual reports of the firms listed on the ASE. The questionnaires and annual reports were employed to collect information from 104 companies in the financial, services, and industrial sectors for this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Studies have suggested that identity verification is one of the factors suggested that can prevent academic fraud whereby it is used by the administration against impersonation during examination (Gathuri, Luvanda, Matende, & Kamundi, 2014;Saheed, Hambali, Adeniji, & Kadri, 2017;Shahwan et al 2022;Sinha, 2022). Impersonation is a significant risk of academic fraud (Erguvan, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have suggested that identity verification is one of the factors suggested that can prevent academic fraud whereby it is used by the administration against impersonation during examination (Gathuri, Luvanda, Matende, & Kamundi, 2014;Saheed, Hambali, Adeniji, & Kadri, 2017;Shahwan et al 2022;Sinha, 2022). Impersonation is a significant risk of academic fraud (Erguvan, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a recent study, Shahwan et al (2022) have done a content analysis of the annual reports of firms listed on the Amman Stock Exchange in order to measure the social responsibility accounting disclosures of these firms. Specifically, content analysis revolves around the notion, that is to access the social responsibility accounting disclosures on the basis of the imprints it has made about it in its published reports like annual reports, business responsibility reports, and sustainability reports (Anderson & Frankle, 1980;Ingram, 1978).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…By these means, the literature concerning this phenomenon did not pick up. Also it was found that only two studies (Shahwan et al, 2022;AL-Hawatmah & Shaban, 2018) were conducted on the social responsibility accounting disclosures in Jordan but these studies were not focused on banks listed on Amman Stock Exchange. The above-mentioned literature makes it clear that the examination of social responsibility accounting disclosures in developing economies is missing and therefore research investigating this phenomenon among the listed banks on Amman Stock exchange is highly relevant.…”
Section: Introductionmentioning
confidence: 99%
“…From another point of view, it can be explained as the accountant's tendency to obtain a high degree of verification to recognize the good news which is greater than the degree of bad news recognition (Ekbal & Al-Qudah, 2014). Meanwhile, (Shahwan, et al, 2022;Al-Madbouli, 2017) believes that accounting conservatism is an accounting principle used by accountants to meet the state of uncertainty and as a consequence, prepare financial statements carefully. So that it does not result in an amplification of income or a reduction in expenses and obligations, and accountants' reliance on more evidence to recognize profits or gains compared to the evidence used to recognize expenses or losses.…”
Section: The Concept Of Accounting Conservatismmentioning
confidence: 99%